High-resolution analyses of recent sediments from a Norwegian mountain lake and comparison with instrumental records of climate - Cameron, NG; Schnell, OA; Rautio, ML; Lami, A; Livingstone, DM; Appleby, PG; Dearing, JA; Rose, NL (KLUWER ACADEMIC PUBL, 2002)
The purpose of the palaeolimnological research project carried out at Ovre Neadalsvatn was to apply a number of physical and biological proxy-climate analyses to recent sediments and to compare the results of these analyses with instrumental records of climate. Using a radiometric chronology to match the sediment core with the calendar ages of the reconstructed instrumental record, and by time-averaging the instrumental record, the statistical significance of the relationships between each of the sediment-climate proxies and the reconstructed instrumental-climate measurements were evaluated.Acid deposition at Ovre Neadalsvatn has been low and its impact limited. Whilst there has been an overall rise in mean annual temperature of about 1 degrees C since 1900, the physical and biological sediment records studied appear to be insensitive to climate warming of this magnitude. On the one hand, this may be a result of the loss in temporal resolution caused by time-averaging the instrumental data; on the other hand, the lake may be insensitive to the impact of this climate change.